2005
DOI: 10.1191/0269215505cr827oa
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of botulinum toxin on lower limb spasticity following acute acquired severe brain injury

Abstract: Active intervention with casting prevents talipes equinovarus deformities in patients losing ankle movement following severe brain injury. Casting alone in these patients is sufficient; the role of additional botulinum toxin needs further investigation, but is safe in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 19 publications
1
62
0
5
Order By: Relevance
“…In this review, we evaluated the outcome in upper limb joints and found that clinical improvement is more consistent for distal joints. A similar evaluation was not performed for the lower limb, as only one study on the lower limb spasticity could be included based on our strict criteria 27 ; the other available trials were excluded because the patients were also treated with casts, 17 or they did not all have post-stroke spasticity, 18 or the data were incomplete. 19 The results of the lower limb spasticity study included showed no significant improvement in walking or spasticity 27 following injection in the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we evaluated the outcome in upper limb joints and found that clinical improvement is more consistent for distal joints. A similar evaluation was not performed for the lower limb, as only one study on the lower limb spasticity could be included based on our strict criteria 27 ; the other available trials were excluded because the patients were also treated with casts, 17 or they did not all have post-stroke spasticity, 18 or the data were incomplete. 19 The results of the lower limb spasticity study included showed no significant improvement in walking or spasticity 27 following injection in the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were excluded because participants were treated with phenol block 15,16 or casts, 17 because not all patients had post-stroke spasticity, 18 or because the data were incomplete. 19 Two trials were reported both as full length publication and as abstract.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
“…The slow progress and the deterioration in right-knee ROM in the first 2 months after admission prompted the move to a more aggressive stretch programme. Serial casting [27][28][29][30] for the right knee therefore began. A series of five casts was applied over 5 weeks.…”
Section: Interventionmentioning
confidence: 99%
“…There are more than 10,000 interesting articles and the relevant papers published every week all over the world contain much more information than the average human brain can assimilate. Even the most recent part of the literature dealing with the impact and safety of botulinum toxin in clinical applications is rather enormous, including short [4], extended [5], classical [6] and new [7,8,9,10,11] articles. An additional difficulty originates from the fact that the research field is spread over a wide range of various and frequently not very much related disciplines such as biochemistry, bioterrorism, chemical synthesis, cosmetics, ecology, medicine, microbiology, neurology.…”
Section: Introductionmentioning
confidence: 99%